Anesthesia Management For Brain Abcess And Hidrocephalus In Children During External Ventrikel Drainage With Tetralogy Of Fallot - Recky Antoni; Vera Muharrami (Green Publisher Indonesia, 2024)
Background: Congenital heart defects occur due to abnormal changes in the structure of the heart that occur early in pregnancy and are present at birth. This defect is the most common congenital anomaly, occurring in approximately 1 in 125 births. Tetralogy of Fallot (TOF) is a defect in which there is an obstruction of blood flow from the heart to the lungs, resulting in low blood oxygen levels. Brain abscess is a rare, fatal complication, accounting for 5%–18.7% of the population with cyanotic congenital heart disease. This condition is often accompanied by headache, fever, seizures, altered mental status, focal neurologic deficits, nausea, and vomiting. Case: A 10 year old girl with brain abcess and hydrocephalus who will undergo external ventrikel drainage with tetralogy of fallot. Disscussion: The Anaesthetic goals for a case of uncorrected Tetralogy of Fallot posted for a non-cardiac surgery are to avoid hypoxemia, ensure adequate hydration, maintain systemic arterial blood pressure (SVR), minimise additional resistance to pulmonary blood flow (pulmonary vascular resistance) and avoiding sudden increase in systemic oxygen demand (cry, inadequate depth of an aesthesia, seizure, pain, etc). Conclution: Anesthesia management of children with TOF presenting for non-cardiac surgery requires a thorough understanding of the pathophysiology of this condition and the altered haemodynamics.